Teknik Dasar Public Speaking dan Penyusunian Materi Presentasi pada Pengelola RPTRA di Jakarta - Dewi, Yuni Retna; Sungkono, Nono; Hamsinah, Hamsinah; Ridwan, Widyarini (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The objective of this community service activity is to equip participants with basic public speaking techniques, confidence, and presentation skills in front of an audience. Participants in this community service consist of RPTRA management staff in Jakarta in accordance with the given theme. The activity was conducted from morning to afternoon and included public speaking lessons, practical exercises/role plays, follow-up plans, and pre-tests to evaluate and provide feedback to each participant. The results of this community service programme showed that participants were able to speak in public, although generally not in a systematic manner. Therefore, an evaluation was conducted based on the pre-test through several questions prepared by the team of instructors. Through this programme, participants were able to maximise their abilities, and it is hoped that this public speaking training programme can be developed further in the future to achieve the goal of building confidence. Thus, it can be concluded that public speaking training can improve participants' knowledge and presentation skills, which in turn can boost their confidence when presenting in public.